Categoric Imperatyve of I. Kant in the Epoch of Jazzing - Jekentaitė, Leonarda (Problemos, 2007)
The way of philosophical thinking has radically changed in our days and sometimes we can name it as the thinking in the style of jazz. The mode of Kant’s three “Critiques” looks too boaring and clumsy in comparison with it, nevertheless they remain on the top of the the human mind‘s achievements till now. Continuing parral between music and thinking we can say, that the essence of this majestic creation can be grasped if it is taken as a musical oneness – the whole “in one achord” (M. Mamardashvili). The spirit of jazz with its ecstatic spontaneity, improvisations and free associations deeply influenced the style of living and the modus of thinking in the Western culture. Now it has more in common with arts and aesthetics, than with the scientific theory, it is more ironic, playful, charming, very often narcissistic, takes examples from visual arts, fiction and films, without the appropriate ethical responsibility. It can be an expression of prevailling ecstatic, empiricaly orientated attitude to the reality. I. Kant reminds us, that the dispersing empirical experience of individual person is the way of passions (Pathos), the pathological way. The sanity of mind depends on the unquestionable respect, responsibility and universalizing force of the highest passion – ethically orientated belief in the humankind in every human being.
Keywords: Kant, Mamardašvili, jazz, pathology, aesthetics, faith